KONSEP PERWAKILAN DI DAERAH UNTUK PENGAMANAN LAUT SEIRING IMPLEMENTASI MILLENIUM DEVELOPMENT GOALS (MDG’s) - Miswan H; Dindin Kurnadi; Dicky R. Munaf (Jurnal Sosioteknologi, 2007)
The Indonesia’s Presidential Decree No. 81 on the revitalization of the maritime Safety Agency (MSA) states that this agency’s main tack and function is to coordinate the policymaking concerning the integrated safety opeations. This task and function is based on the sustainable development pronciples and the goals of the Indonesia people’s welfare. In relation to the task and function, MSA sets up its regional representative councils in three different sea water territories of Indonesia’s islands.